PENGARUH ONLINE CUSTOMER REVIEW DAN ONLINE CUSTOMER RATING TERHADAP KEPUTUSAN PEMBELIAN SUNSCREEN WARDAH MARKETPLACE SHOPEE DI KOTA BANJARMASIN - Radhyna Emalia Febriyani; Novia Nour Halisa; Setio Utomo; Irwansyah (Business Administration, FISIP ULM, 2025)
This study uses a quantitative methodology. The location of the research is in the city of Banjarmasin. A sample of 110 respondents who had purchased decisions for Wardah sunscreen on the Shopee marketplace in the city of Banjarmasin with data collection using questionnaires and data analysis using multiple linear regression analysis. The results of this research show that online customer reviews have a partially significant effect on purchasing decisions for Wardah sunscreen on the Shopee marketplace in the city of Banjarmasin. Then, online customer rating has a partially significant effect on purchasing decisions for Wardah sunscreen on the Shopee marketplace in the city of Banjarmasin. Also, online customer reviews and online customer ratings simultaneously have a significant influence on purchasing decisions for Wardah sunscreen on the Shopee marketplace in the city of Banjarmasin.